PARTISIPASI PETANI ANGGOTA P3A DALAM PENGELOLAAN AIR DI DESA BANDAN HURIP DAN PALAS JAYA, KECAMATAN PALAS KABUPATEN LAMPUNG SELATAN - Muhammad Faiq Saputra; Dewangga Nikmatullah; Muhammad Ibnu (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This study aims to analyze the level of participation of P3A member farmers in irrigation water management, to find out the variables that affect the level of the participation, and to find out the implications of research findings on irrigation water management.  The research location was chosen deliberately in the villages of Bandan Hurip and Palas Jaya, Palas Subdistrict, South Lampung Regency.  The research was carried out in June 2018 using a survey method. The number of respondents was 82 P3A members determined using the Slovin formula.  The level of participation of P3A members was analyzed descriptively, the variables affecting the level of the participation were analyzed using ordinal logistic regression, and the implications of the research findings were analyzed using qualitative descriptive analysis.  The results showed that the highest level of participation of P3A members in water management was 43.90% at the low classification level.  The variables that influence the level of the participation in irrigation water management are the member interaction and the members’ motivation, while variables that do not affect are the group's role, level of knowledge, and members’ activity.Key words: participation, P3A, water management